Analyzing metaheuristic methods to build an optimal composite foot prosthesis insole - Álvaro Gustavo Rodríguez (International Journal of Advanced Science and Computer Applications, 2022)
This paper uses metaheuristic algorithms to develop and optimize composite materials. To calculate the characteristics that allow the planned item to withstand particular loads, ABC and Differential Evolution algorithms are utilized. One of the key challenges in these designs is determining the piece's thickness. Designing a carbon fibre insole for Latin American users will improve the design process by generating functional solutions that are feasible to manufacture and in less time than traditional design methods. The results reported in this work demonstrate that a functional design may be developed, validated by finite element method, with minimal material waste and in a reasonable period.